Interrupting Kant’s Dogmatic Slumber - Dunlop, Katherine (Con-Textos Kantianos. International Journal of Philosophy, 2022)
Review of:  Anderson, Abraham, Kant, Hume, and the Interruption of Dogmatic Slumber, New York, Oxford University Press, 2020, 180+xxii, 978-0-19-009674-8